The Accountant's Stereotype: Real or Imagined, Deserved or Unwarranted. - DeCoster, Don T.; Rhode, John Grant; Gaines, Michael B.; Murphy, Edward H. (The Accounting Review, 1971)
This article examines selected personality characteristics of certified public accountants (CPA). The literature provides evidence that accountants are negatively stereotyped as cold, aloof, nonsociable, submissive, shallow, weak, passive and lacking sensitivity. There are conflicting data regarding the appropriateness of the stereotype since some studies give segmented support while others deny its existence. Comparisons of personality characteristics, as measured by the California Psychological Inventory, were made between eight different occupational groups and an accounting sample of fifty-six CPA firm employees to test the appropriateness of the stereotype. The comparisons revealed that CPA firm employees possessed higher personality profiles when compared to samples of salesmen, bank managers, business executives, city school superintendents, architects and military officers–partially denying the validity of the accountant's stereotype as dull, wary, cold, and aloof. When contrasted with practicing dentists and research scientists, the accountants generally scored lower on the test scales. The more extensive education of these two groups account for the difference. The negative attributes of poor interpersonal relations and socialization simply did not surface. Since the CPA firm employees significantly higher than several comparison groups on the sociability, self-acceptance, socialization, self-control, good impression, psychological-mindedness and flexibility scales. The accountant's stereotype may not only be unwarranted, it may also be inappropriate.